Adaptive fuzzy tracking control of robot manipulators actuated by permanent magnet synchronous motors. (November 2018) - Khorashadizadeh, Saeed; Sadeghijaleh, Mahdi
Abstract: This paper presents a model-free controller for robot manipulators driven by permanent magnet synchronous motors (PMSM). The contribution of this paper is merging the electrical and mechanical equations of the robotic system to simplify the controller design procedure. In other words, due to the fact that the manipulator links are the load torques of the PMSMs, the uncertainties related to the manipulator dynamics have been transferred to the voltage equations of the PMSMs. Uncertainties including external disturbances and system dynamics are estimated and compensated in the control law using adaptive fuzzy systems. In contrast to most previous related works that ignore the PMSM electrical equations, both the electrical and mechanical equations are taken into consideration. Based on the Barbalat's lemma, the asymptotic convergence of the tracking error to zero is guaranteed. The case study is an articulated manipulator driven by PMSMs. In comparison with a robust controller for a single-link manipulator actuated by PMSM, the proposed method is superior due to faster and smoother responses.